Catecholamines in Alzheimer's Disease: A Systematic Review and Meta-Analysis - Pan, Xiongfeng; Kaminga, Atipatsa C.; Jia, Peng; Wen, Shi Wu; Acheampong, Kwabena; Liu, Aizhong (Frontiers in Aging Neuroscience, 2020)
Background and Purpose: Previous studies found inconsistent results regarding the relationship between AD and catecholamines, such as dopamine (DA), norepinephrine (NE), and epinephrine (EPI). Our study performed a systematic review and meta-analysis to evaluate previous studies’ results on this relationship. Method: Literature retrieval of eligible studies was performed in 4 databases (Web of Science, PubMed, Embase, and Psyc-ARTICLES). Standardized mean differences (SMD) were calculated to assess differences in catecholamines between the AD groups and controls. Results: Thirteen studies met the eligibility criteria. Compared with the controls, significant lower levels of NE (SMD=-1.10, 95% CI: -2.01 to -0.18, p=0.019) and DA (SMD =-1.12, 95% CI: -1.88 to -0.37, p=0.003) concentrations were observed in patients with AD. No difference was found in EPI (SMD=-0.74, 95% CI: -1.85 to 0.37, p=0.189) between the two groups. Conclusion: Overall, these findings are in line with the hypothesis that reduced NE and DA may be an important indicator for AD. (Registration number CRD42018112816)